Strategy and Strategic Leadership in Education: A Scoping Review - Carvalho, Marisa; Cabral, Ilídia; Verdasca, José Lopes; Alves, José Matias (Frontiers in Education, 2021)
Strategy and strategic leadership are critical issues for school leaders. However, strategy as a field of research has largely been overlooked within the educational leadership literature. Most of the theoretical and empirical work on strategy and strategic leadership over the past decades has been related to non-educational settings, and scholarship devoted to these issues in education is still minimal. The purpose of this scoping review was to provide a comprehensive overview of relevant research regarding strategy and strategic leadership, identifying any gaps in the literature that could inform future research agendas and evidence for practice. The scoping review is underpinned by the five-stage framework of Arksey and O'Malley (2005). The results indicate that there is scarce literature about strategy and that timid steps have been made toward a more integrated and comprehensive model of strategic leadership. It is necessary to expand research into more complex, longitudinal, and explanatory ways due to a better understanding of these constructs.